Dedifferentiated laryngeal chondrosarcoma: Combined morphologic and functional imaging with positron‐emission tomography/magnetic resonance imaging. (18th December 2013) - Purohit, Bela S.; Dulguerov, Pavel; Burkhardt, Karim; Becker, Minerva
<x xml:space="preserve">Abstract</x> Chondrosarcoma of the larynx is a rare, low‐grade malignancy in terms of histology and clinical behavior. We present an unusual case of laryngeal chondrosarcoma, which developed a large dedifferentiated component on recurrence after primary surgery. The diagnosis of dedifferentiation was suggested in view of the morphological and metabolic findings on hybrid positron‐emission tomography/magnetic resonance imaging (PET/MRI) and was subsequently confirmed surgically. Whole‐organ, slice‐by‐slice radiologic–histologic correlation revealed excellent delineation of the well‐differentiated and dedifferentiated tumor components with PET/MRI. PET/MRI can provide additional functional information to supplement the morphological mapping and histopathology of these tumors. Laryngoscope, 124:E274–E277, 2014